Penggunaan Teks Cerita Dalam Pengajaran Keterampilan Berbicara Di Lembaga Kursus Bahasa Arab Ocean Pare Kediri - Yazid Albustomi, Muhamad; Setyabudi, M. Arif (Menara Tebuireng, 2024)
Abstract—“The process of implementing the Story Method at the OCEAN Arabic Language Education Institute in Tulungrejo Pare Kediri Village for the 2022/2023 academic year East Java, have good bi'ah lughowiyah discipline, and students are able to compose Arabic stories spontaneously in a short time. Based on the facts above, the researcher used a qualitative descriptive study which had the aim of knowing and learning incentives about the application of the learning process using Arabic stories so that students who had taken courses there in a short time could master speaking skills well. Data collection techniques in this study used triangulation. Methods of data collection using observation, interviews, and documentation. The research formulation consists of: 1). How to Use the Story Method for Students at the OCEAN Pare Kediri Arabic Course Institute?. 2). How are the Speaking Skills of Students at the OCEAN Pare Kediri Arabic Language Course Institute?. 3). What are the supporting and inhibiting factors for learning Arabic using the story method for students at the OCEAN Pare Kediri Arabic Language Course? The results of this study are 1). The application of the Story Method at the Pare Kediri OCEAN Arabic Course Institute was carried out in several stages. Namely memorizing mufrodats, making simple sentences, retelling Arabic books that have been read, and composing stories from all the mufrodats that have been obtained. 2). Students who are at the OCEAN Arabic Language Course institution have good language skills, are able to communicate spontaneously according to the Arabic language course, and are active in speaking both inside and outside the bi'ah lughowiyah area. 3). Supporting factors in learning Arabic for students using the story method at the OCEAN Arabic Language Institute are a supportive environment, the availability of many story books, and a high enthusiasm for learning. The inhibiting factors are the differences in the capacity of students' Arabic proficiency, and the lack of some student literacy.” Keyword: Story Method, Bi'ah Lughowiyah, Speaking Skills.